Exploring seed characteristics and performance through advanced physico-chemical techniques - Dhanalakshmi Vadivel; Rania Djemal; Jessica García; Andrea Pagano; Rahma Trabelsi; Maroua Gdoura-Ben Amor; Safa Charfeddine; Siwar Ghanmi; Ibtisem Khalifa; Mariem Rekik; Fatma Amor; Chantal Ebel; et al. (Scientific Reports)
Abstract Simple physico-chemical techniques can be used to evaluate the composition, structure, and characteristics of plant seeds to determine their viability, quality, and possible uses in agriculture. Advanced analytical techniques, including thermo gravimetric analysis (TGA), electron paramagnetic resonance (EPR), and high-pressure liquid chromatography (HPLC), provide completely new insights and more precise information. They can be integrated to build up seed quality profiles, with great advantage to assess water content, organic compounds, and inorganic metals without the need to carry out many extraction procedures, as requested by more conventional methods. In this study, seed lots from three different plant species such as Triticum turgidum L. subsp. durum (wheat), Trigonella foenum graecum L. (trigonella or fenugreek), and Atriplex halimus L. (saltbush or sea orach) have been used to test the potential of TGA, EPR, and HPLC to discriminate between seed-specific features. A key finding of this study is that HPLC is essential in Principal Component Analysis (PCA) because various seeds (from the same species or other species) may contain compounds with varying polarity groups. The reported data confirm the efficacy of this approach. These data, fully available for other users, are coherently constructed and provide a proof of concept for future seed quality control studies.